2007
DOI: 10.1007/s00381-007-0339-0
|View full text |Cite
|
Sign up to set email alerts
|

Change in cerebral autoregulation as a function of time in children after severe traumatic brain injury: a case series

Abstract: Cerebral autoregulation often changed and worsened during the first 9 days after severe pediatric TBI. Worsening cerebral autoregulation may mirror worsening TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 20 publications
0
17
0
1
Order By: Relevance
“…Our study of moderate to severe pediatric TBI shows that hemispheric differences in cerebral autoregulation are common (40%) after focal TBI, and that, cerebral autoregulation may be impaired in those hemispheres without radiographic evidence of TBI (unpublished data). Furthermore, a recent study of severe pediatric TBI reported that cerebral autoregulation often changed and worsened during the first 9 days after injury, and that worsening cerebral autoregulation may mirror worsening TBI [105].…”
Section: Impaired Cerebral Pressure Autoregulationmentioning
confidence: 99%
“…Our study of moderate to severe pediatric TBI shows that hemispheric differences in cerebral autoregulation are common (40%) after focal TBI, and that, cerebral autoregulation may be impaired in those hemispheres without radiographic evidence of TBI (unpublished data). Furthermore, a recent study of severe pediatric TBI reported that cerebral autoregulation often changed and worsened during the first 9 days after injury, and that worsening cerebral autoregulation may mirror worsening TBI [105].…”
Section: Impaired Cerebral Pressure Autoregulationmentioning
confidence: 99%
“…Impaired cerebral autoregulation is common following TBI and has been reported in 29 to 63% of pediatric patients [60][61][62][63]. Young age (less than 5 years) appears to be a risk factor [64,65].…”
Section: Current Controversiesmentioning
confidence: 99%
“…During the first 0-9 days cerebral autoregulation is often impaired following a TBI, this results in CBF becoming dependent on cerebral perfusion pressures (CPP) and ICP (Tontisirin et al, 2007). An increased risk for impaired autoregulation has been associated with increased ICP, hyperemia, decreased hematocrit, decreased arterial oxygen (PaO 2 ), increased cerebral lesion size, and are less than 4 years of age (Freeman, Udomphorn, Armstead, Fisk, & Vavilala, 2008;Tontisirin et al, 2007). Clinically, children with impaired cerebral autoregulation have increased odds of poor outcomes (e.g., functional impairment, vegetative state, or death) (Tontisirin et al, 2007).…”
Section: Secondary Injurymentioning
confidence: 99%